Temporary Ovarian Suppression With Gonadotropin-Releasing Hormone Agonist During Chemotherapy for Fertility Preservation: Toward the End of the Debate? - Del Mastro, Lucia (Oncologist, 2015)
Temporary ovarian suppression with gonadotropin-releasing hormone agonist during chemotherapy might be a reliable strategy not only to preserve ovarian function but also to increase the likelihood of becoming pregnant after the end of cytotoxic therapy. The findings of Blumenfeld et al. are consistent with recent data suggesting the efficacy of this strategy in preserving fertility.